Adaptability and Stability of Elite Potato (Solanum tuberosum. L) Genotypes in Kenya (Global Journal of Science Frontier Research, 2020)
This study evaluated the adaptability and stability of twenty-three Table and Processing potato genotypes. The experiments were conducted in six test environments during 2015 and 2016 sowing seasons, in a randomized complete block design of three replications. Data was analyzed with Genotype, Genotype Environment (GGE) biplot. The results indicated that G2 Processing and G15 Table genotypes were adapted in Burnt forest whereas G5 Table and G26 Processing types were adapted to the Molo environment. Genotypes, G22 of Processing and G6 of Table types were the most stable whereas, G2 of Processing and G15 of Table types were the most unstable. The results showed that the GGE biplot is a useful tool of analyzing genotype x environment interactions.
Keywords: adaptability; GGE biplot; stability and tuber yield